Penerapan Analisis OODA Loops Pada Strategi Ketahanan UMKM Melalui Pemanfaatan Media Sosial Dengan Pendekatan TOE Framework - Theorupun, Milka Susana; Pratiwi, Yunita Niqrisah Dwi; Setiawati, Donna (Universitas Hamzanwadi, 2025)
This study aims to analyze the application of OODA Loop analysis in the resilience strategy of Micro, Small, and Medium Enterprises (MSMEs) through the use of social media, with the TOE Framework (Technology, Organization, and Environment) approach. With increasing competition in the digital era, MSMEs need to adopt adaptive and responsive strategies to survive and thrive. This study uses a qualitative method with interviews and surveys of a number of MSMEs that are active on social media. Data analysis uses 2 (two) methods, namely OODA Loops and TOE Framework. The results of the study show that the application of OODA Loop analysis helps MSMEs in observing market conditions, orienting strategies, making the right decisions, and acting efficiently. Social media functions as a vital tool in the process of observation and interaction with customers, allowing MSMEs to respond quickly to consumer needs and preferences. The TOE Framework approach highlights the importance of technological, organizational, and environmental factors in facilitating the implementation of OODA Loop, where technological support and innovative organizational culture are the keys to success. The results of the study show that this approach can significantly improve the responsiveness and adaptability of MSMEs in a dynamic market and create a comprehensive framework to improve the resilience and competitiveness of MSMEs. The advice given is for MSMEs to continue to develop digital capacity and adapt to environmental changes to achieve sustainability and competitive advantage in the market.